Integrated immunohistochemical and DNA copy number profiling analysis provides insight into the molecular pathogenesis of canine follicular lymphoma. (2nd May 2016) - Thomas, R.; Demeter, Z.; Kennedy, K. A.; Borst, L.; Singh, K.; Valli, V. E.; Le Boedec, K.; Breen, M.
Abstract: Follicular lymphomas (FLs) typically exhibit a chromosome translocation that induces constitutive expression of the anti‐apoptotic bcl2 protein and accumulation of additional molecular defects. This rearrangement offers a promising therapeutic target, but its nature as a fundamental driver of FL pathogenesis remains unclear as 15% of cases lack the translocation. We performed an integrated immunohistochemical and genomic investigation of 10 naturally occurring FL cases from domestic dogs, showing that, as with human tumours, they exhibit marked heterogeneity in the frequency and intensity of bcl2 protein expression. Genomic copy number aberrations were infrequent and broadly consistent with those of other canine B‐cell lymphoma subtypes. None of the canine FL specimens exhibited a rearrangement consistent with the hallmark translocation of human FL, despite their remarkable histomorphologic similarity. Parallel exploration of canine and human cases may reveal alternative tumour‐initiating mechanisms other than BCL2 disruption, yielding a more complete definition of the molecular pathogenesis of FL.